FEATURES OF FINANCIAL SUPPORT FOR THE REAL SECTOR OF UZBEKISTAN’S ECONOMY IN THE CONTEXT OF GEO-FINANCIAL POLICY INSTABILITY - Ilnur Suleymanov (Journals Park Publishing, 2024)
The article sheds light on aspects of monetary and credit policy and its impact on Uzbekistan's economy, with an emphasis on the capitalization of banks and their role in financing the real sector of the economy. It outlines measures aimed at strengthening the effectiveness of monetary and credit policy, including increasing the level of capitalization of commercial banks, which is considered a key factor in the stability of the banking system. Data on the significant growth of the total capital of commercial banks in 2017 and the increase in their charter capital are provided. The article also underscores the importance of integrating the banking and real sectors of the economy, pointing out strategic measures taken to strengthen this integration. Special attention is given to the analysis of financial support from commercial banks in Uzbekistan to enterprises in the real sector, including changes in the volumes of credit operations. Additionally, various forms of lending to sectors of the real economy, including industry, agriculture, and construction, are examined. Changes in the credit portfolios of major commercial banks over several years are described, as well as general trends in lending, including an increase in the proportion of problem loans and changes in the structure of funding sources. The article discusses the investment policy of the banking system and its impact on economic stability and offers recommendations for improving financial security and integration of the banking sector with the real sector of the economy.
Keywords: Bank Capitalization, Financial Stability, Real Sector Financing, Banking System Integration, Credit Portfolio Analysis, Investment Policy, Economic Impact, Sector-specific Lending (Industry, Agriculture, Construction).